2001
DOI: 10.1007/s004140100226
|View full text |Cite
|
Sign up to set email alerts
|

Expression of paraoxonase isoform did not confer protection from acute sarin poisoning in the Tokyo subway terrorist attack

Abstract: We previously reported the polymorphism of the high density lipoprotein-associated enzyme paraoxonase (PON1), in the 10 sarin poisoning victims in the Tokyo subway terrorist attack. Arg192 PON1, which has low sarin hydrolysing activity, was found to be more common in the Japanese population than in people of other races. However, from our analyses seven of the victims expressed the PON1 phenotype with high sarin hydrolysing activity and three with low sarin hydrolysing activity. These results indicate that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…In recent years, some studies have started to investigate the potential role of PON1 in modulating the toxicity of OPs in humans. Such studies have dealt primarily with the nerve agent sarin, in relationship to exposure in the terrorist attacks in Japan (Yamada et al, 2001) or the Gulf War Syndrome (Haley et al, D. L. EATON ET AL. 2000; Mackness et al, 2000), and diazinon, in relationship to the use of this OP in sheep dipping (Cherry et al, 2002;Mackness et al, 2003). These studies are discussed in detail elsewhere (Costa et al, 2003).…”
Section: Iic5 Paraoxonase (Pon1)mentioning
confidence: 99%
“…In recent years, some studies have started to investigate the potential role of PON1 in modulating the toxicity of OPs in humans. Such studies have dealt primarily with the nerve agent sarin, in relationship to exposure in the terrorist attacks in Japan (Yamada et al, 2001) or the Gulf War Syndrome (Haley et al, D. L. EATON ET AL. 2000; Mackness et al, 2000), and diazinon, in relationship to the use of this OP in sheep dipping (Cherry et al, 2002;Mackness et al, 2003). These studies are discussed in detail elsewhere (Costa et al, 2003).…”
Section: Iic5 Paraoxonase (Pon1)mentioning
confidence: 99%
“…As the prevalence of the PON1 R192 genotype in the Japanese population is 0.66 (Yamasaki et al, 1997), compared with 0.25 to 0.30 in various Caucasian populations (Brophy et al, 2002), Japanese individuals may have been more prone to sarin toxicity. However, a small-scale study suggested that the genotype (192Q) that confers high hydrolyzing activity toward sarin did not appear to provide protection from acute sarin poisoning (Yamada et al, 2001). It should be noted that, at least in a Caucasian population, the range of sarinase activity among individuals with the QQ or QR genotype ranged from 0 to 758 U/L (Davies et al, 1996), and no determination of PON1 status was done in the Yamada et al, (2001) study.…”
Section: Pon1 Status and Op Toxicity: Evidence In Humansmentioning
confidence: 99%
“…However, a small-scale study suggested that the genotype (192Q) that confers high hydrolyzing activity toward sarin did not appear to provide protection from acute sarin poisoning (Yamada et al, 2001). It should be noted that, at least in a Caucasian population, the range of sarinase activity among individuals with the QQ or QR genotype ranged from 0 to 758 U/L (Davies et al, 1996), and no determination of PON1 status was done in the Yamada et al, (2001) study. Furthermore, the catalytic efficiency of sarin hydrolysis by PON1 is low, a situation thus similar (though reversed) to that of paraoxon.…”
Section: Pon1 Status and Op Toxicity: Evidence In Humansmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the Tokyo subway sarin attack, an analysis of PON1 192 polymorphisms was carried out on 10 casualties (Yamada et al, 2001). As mentioned, the R allele has been shown to superiorly hydrolyze sarin and thus would be predicted to confer a degree of protection from poisoning.…”
Section: Paraoxonasementioning
confidence: 99%